2017
DOI: 10.1242/bio.022954
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral evidence for a magnetic sense in the oriental armyworm,Mythimna separata

Abstract: Progress has been made in understanding the mechanisms underlying directional navigation in migratory insects, yet the magnetic compass involved has not been fully elucidated. Here we developed a flight simulation system to study the flight directionality of the migratory armyworm Mythimna separata in response to magnetic fields. Armyworm moths were exposed to either a 500 nT extreme weak magnetic field, 1.8 T strong magnetic field, or a deflecting magnetic field and subjected to tethered flight trials indoors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…My. separata might actually possess corresponding arrangements as well, since it is reported to maintain consistent directions when migrating ( Xu et al, 2017 ). Generally, the antennal sensilla of My.…”
Section: Discussionmentioning
confidence: 99%
“…My. separata might actually possess corresponding arrangements as well, since it is reported to maintain consistent directions when migrating ( Xu et al, 2017 ). Generally, the antennal sensilla of My.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of a magnetic compass for long-distance migration in birds [9], sea turtles [12], and fish [13] has been long established, its role in long-distance migration in insects is unknown. Tentative evidence suggests that some migratory moths may sense magnetic fields [14][15][16], as may some butterflies [17,18], such as the diurnal long-distance migratory monarch butterfly, Danaus plexippus [18], although in many of these studies very strong (unnatural) magnetic fields were used to show effects and the evidence is also conflicting [7,19]. Hitherto studied migratory butterflies instead appear to rely primarily on a sun compass [7,[20][21][22], and it remains unclear how, or whether [19], they use the Earth's magnetic field for navigation in natural circumstances.…”
Section: The Earth's Magnetic Field and Visual Landmarks Steer Migratory Flight Behaviormentioning
confidence: 99%
“…Accordingly, it has been confirmed that a magnetic compass was involved in both species (Srygley et al 2006;Guerra et al, 2014. It is also the case for some migratory moths as the Mythimna separata that maintain migratory direction in the night sky (Xu et al, 2017). The use of magnetic compass has also been found in foraging of insects, including honeybee and ants.…”
Section: Introductionmentioning
confidence: 99%